MANFAAT DIKLAT DALAM PEMBUATAN MEDIA INTERAKTIF UNTUK GURU DI JENJANG SEKOLAH MENENGAH PERTAMA - Nur Iman Putri Kertamuda; Muhammad Nurwahidin; Riswandi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
In educational institutions, the main human resource is the teacher. Teachers play a vital role as they are directly involved in the teaching-learning process and the development of learners' potential. Teacher performance affects the quality of learning provided to students. To improve teacher performance, training is required. Training is an acronym for education and training. The purpose of this article is to describe the benefits of interactive training in making media for junior high school teachers. This finding uses the Systematic Literature Review (SLR) method. The initial data obtained were 34 articles on the benefits of training in 2020-2024. After going through a screening process based on criteria, 19 articles were discarded, because they did not have a Sinta database. The results of the article screening showed that there were 15 articles that were analyzed. The results show that training in making interactive media is beneficial and has a positive impact on teachers at the junior high school level. The training not only increases teachers' knowledge and skills, but also their motivation and creativity in teaching.